Pola Konsumsi Dan Tumbuh Kembang Balita Usia 24-60 Bulan Di Wilayah Kerja Puskesmas Cebongan, Kota Salatiga - Rifatolistia Tampubolon; Kukuh Pambuka; Maria Dyah Kurniasari; Yulce Desiana Waisimon; Gelora Mangalik (Jurnal Keperawatan Muhammadiyah, 2020)
Growth and development is influenced by children consumption and parenting patterns. The prevalence of toddler malnutrition in Salatiga is still being targeted by the Millennium Development Goals (MDGs) in 2015. This study aims to look at feeding, growth and development patterns of toddler in the Cebongan Community Health Center Salatiga working area. The design of this study uses quantitative with a descriptive approach. The population was 631 toddlers aged 24-60 months with a total sample of 251 toddlers using the Slovin formula. Data collection techniques with cross sectional approach. The instruments in the study used the Denver Development Scrining Test (DDST), anthropometric measurements, and food frequency questionnare (FFQ). The results of this study indicate that there is an influence between consumption patterns and growth and development of toddlers and parenting patterns. The result was seen in the measurement of nutritional status in toddler growth found the prevalence of underweight (7%), short (17.5%), thin (15%), the results of the development test suspect (8%) and toddlers with normal categories (52.5%). The consumption patterns of toddlers are influenced by the mood of toddlers who like to choose foods according to their want and parenting patterns of parents who follow the want of children who can affect the nutritional status and growth and development of toddlers to be good and bad.